1999
DOI: 10.1128/jvi.73.6.5056-5063.1999
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Nontypical Apoptotic Morphological Changes Visualized by Green Fluorescent Protein in Living Cells with Infectious Pancreatic Necrosis Virus Infection

Abstract: Morphologically, apoptotic cells are characterized by highly condensed membrane blebbing and formation of apoptotic bodies. Recently, we reported that apoptosis precedes necrosis in a fish cell line infected with infectious pancreatic necrosis virus (IPNV). In the present study, we tested the possibility that nontypical apoptosis is a component of IPNV-induced fish cell death. A variant type of green fluorescent protein (EGFP) was expressed in a fish cell line such that EGFP served as a protein marker for visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…Severely affected livers in the current study showed apoptosis could be combined with a spreading necrosis and loss of structure throughout large areas of the tissue. The induction of apoptosis by IPNV has been investigated in vitro in fish cell lines (Hong, Lin, Hsu & Wu 1998a,b; Hong, Hsu & Wu 1999b; Hong, Lin, Yang, Hsu & Wu 1999a; Hong & Wu 2002; Chen et al. 2009), in vivo through experimental studies in salmon by Santi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Severely affected livers in the current study showed apoptosis could be combined with a spreading necrosis and loss of structure throughout large areas of the tissue. The induction of apoptosis by IPNV has been investigated in vitro in fish cell lines (Hong, Lin, Hsu & Wu 1998a,b; Hong, Hsu & Wu 1999b; Hong, Lin, Yang, Hsu & Wu 1999a; Hong & Wu 2002; Chen et al. 2009), in vivo through experimental studies in salmon by Santi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of CHSE-214 with IPNV isolate E1-S upregulates the host survival factor Mcl-1, which may enhance viral progeny production and may block caspase activity, but details are still lacking. This phenomenon may explain how convergent viral evolution ablates the host response by targeting strategic points in specific defence pathways and thus inhibits or delays protective mechanisms until sufficient viral yields have been produced (Hong et al , 1999a. Why VP5 has lost its protein function and how apoptosis responses are regulated in the host cell in the early virus replication cycle needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos at the one- or two-cell stage were injected with YY1-MO (25 ng) or control-MO (25 ng) or YY1-MO (25 ng) plus PSR mRNA (1 ng), harvested at 18.5 hpf, fixed with 4 % paraformaldehyde in PBS (pH 7.4) at room temperature for 30 min, stained with acridine orange (1 μg.ml −1 ; 3–5 min), washed twice in PBS, and evaluated under a fluorescence microscope (using a 488-nm filter for excitation and a 515-nm long-pass filter for detection) [ 44 ]. For the TdT-dUTP labeling step, the embryos were fixed in paraformaldehyde at the end of the incubation period (12 and 24 hpf), dechorionated, incubated in blocking solution (0.1 % H 2 O 2 in methanol, 30 min, room temperature), rinsed with PBS, incubated on ice in 0.1 % Triton X-100 in 0.1 % sodium citrate for 30 min to increase permeability, rinsed twice with PBS, treated with TUNEL reaction mixture (50 μl; in-situ cell death-detection Kit, Boehringer Mannheim), incubated in a humidified chamber for 60 min at 37 °C, and evaluated for fluorescence-positive apoptotic cells under a fluorescence microscope equipped with a spot II CCD camera (Diagnostic Instruments, Inc., Sterling Heights, MI).…”
Section: Methodsmentioning
confidence: 99%
“…Standard western-blot analysis was conducted using human anti-YY1 Mab (Cascade Bioscience, Winchester, MA), anti-zebrafish PSR N-terminus polyAb (self-made), and mouse anti-actin Mab (Chemicon, Temecula, CA). PSR was visualized using horseradish peroxidase-conjugated anti-mouse immunoglobulin (IgG) and the ECL detection kit (Amersham Pharmacia Biotech, Denmark) [ 44 ].…”
Section: Methodsmentioning
confidence: 99%